The Impact of Covid-19 Pandemic to the Construction Industry in Malaysia - Muhammad Riza, Nurirdina Maisarah; Abdul Latiff, Muhammad Farhan Haqimi; Hamzah, Muhammad Aiman; Idris, Nur'Ain (Multidisciplinary Applied Research and Innovation, 2022)
COVID-19 is an infectious disease caused by a newly discovered strain of coronavirus; a type of virus known to cause respiratory infections in humans. This new strain was unknown before December 2019, when an outbreak of pneumonia of unidentified cause emerged in Wuhan, China. The first case of COVID-19 in Malaysia was detected on 24 January 2020.  The World Health Organization (WHO) Country Office in Malaysia has been working closely with the Ministry of Health to respond to this outbreak.  The National Security Council of Malaysia (MKN) enforced a Movement Control Order (MCO) started on March 2020 to break the chain of COVID-19. Malaysia has facing it more than a year since the arrival of COVID-19. Thus, the country’s economic growth has lowered down and affected many industries including the construction industry. Most of developments and construction projects were delayed due to this pandemic issues. Therefore, this study was conducted with the purpose to investigate the impact of COVID-19 pandemic to construction industry in Malaysia. The study implied a questionnaire surveys method using Google Form and involved of 79 respondents coming from the construction industry. Then the results obtain was analyzed using Microsoft excel and Likert scale. From the study, the most prominent impacts of COVID-19 found are the salary deducted, forbid to go to the construction site, projects delayed, lost of job, and new cluster of Covid-19 among the construction industry. The findings also help project stakeholders to realize the sequences of the sudden epidemic and prepare for the worst-case scenario during the planning stage of construction projects. The effect of COVID-19 pandemic towards construction industry is predicted to have long term impact especially in development and economic growth.